The Comparative Study of Taxation Systems and Their Impact on National Financial Stability - Fhikry Ahmad Halomoan Siregar; Mela Novita Rizki; Sattar Rasul (International Journal of Advanced Research, 2024)
This study examines the comparative impact of different taxation systems on national financial stability. By analyzing progressive, regressive, and proportional tax structures across a range of countries, the research identifies that progressive taxation systems are more effective in promoting fiscal stability and reducing income inequality. Countries with progressive tax policies, such as Sweden and Denmark, demonstrate higher revenue generation and greater investments in social welfare programs, which foster long-term economic growth and stability. In contrast, regressive tax systems, common in developing nations, often lead to income disparities and inadequate public services, destabilizing national finances. The study also highlights the role of tax compliance, institutional strength, and governance in ensuring the success of tax systems. Furthermore, tax reforms are crucial for improving tax collection efficiency and enhancing financial health, as seen in countries like South Korea and Chile. The research suggests that tax systems must be tailored to the specific economic, social, and political contexts of each country, with a focus on equity, efficiency, and sustainability. Ultimately, this study emphasizes that well-designed taxation policies are essential for maintaining long-term financial stability and fostering sustainable economic growth.